Balance assessment with smartphone devices in para-footballers with cerebral palsy - Cornejo, M. I.; Roldan, A.; Barbado, D.; Reina, R. (Journal of Science and Medicine in Sport, 2024)
Objectives To explore whether the mean lumbar acceleration is a feasible tool for determining minimum eligibility criteria to compete in cerebral palsy football, differentiating between new sports classes, and to assess the effect of foot contacts on balance evaluation and class distinction.